HUBUNGAN ANTARA HIPERKOLESTEROLEMIA DENGAN NYERI KEPALA TIPE TEGANG - Adi Puspowati, Herlina Suryawati, Dwi Pudjonarko (NEURONA, 2014)
INTRODUCTION TENSIONTYPE HEADACHE TTH HAS THE GREATEST PREVALENCE OF OVERALL HEADACHE ORIGINATED FROM INFREQUENTEPISODIC AND FREQUENT TO CHRONIC THE RESULT IS A CHRONIC CENTRAL SENSITIZATION INFLAMMATORY PROCESS THAT OCCURS IS AFFECTED BY THE MECHANISM OF NO NITRIC OXIDE THROUGH A HIGHCHOLESTEROL DIET